Sintesis dan Karakterisasi Hidrogel Kitosan-Minyak Jintan Hitam (Nigella sativa L.)-Lendir Bekicot (Achatina fulica) - Shabrina Dwi Ardinimia; Sari Edi Cahyaningrum (Unesa Journal of Chemistry, 2026)
Wounds that are not treated promptly can become infected with bacteria, which prolongs the healing process. The bacterial species most commonly associated with wound infections is Staphylococcus aureus, found in 6.3% to 56.6% of wound infection cases. One preventive measure against infection is the application of topical preparations containing antibacterial compounds such as chitosan, black cumin oil, and snail mucus. This study aims to synthesize and characterize hydrogel formulations based on chitosan, black cumin oil, and snail mucus. The hydrogels were prepared in four formulations with varying concentrations of black cumin oil: F0 (0%), F1 (5%), F2 (7%), and F3 (9%). The characterization included physical property tests, such as spreadability, adhesion, and homogeneity. As well as chemical property tests, including pH measurement and functional group analysis using FTIR. The results showed that all formulations exhibited homogeneous physical characteristics and met the standards for topical preparations. The hydrogels’ spreadability met the ideal criteria (5,18 ± 0,01 – 5,38 ± 0,02 cm), and their adhesion increased with rising black cumin oil concentration (32,67 ± 0,58 – 59,00 ± 1,00 seconds). The hydrogels’ pH values ranged from 6,16 ± 0,03 to 6,89 ± 0,01, which is consistent with skin pH. Functional group analysis revealed the presence of O-H, N-H, C-H, C=O, C=C, C-O, and C-N stretching vibrations. These hydrogel formulations demonstrate promising initial physicochemical characteristics, although further biological evaluation is still required.